Performance of A Regenerative Tuned Mass Damper for An Electric Vehicle Under Varying Road Condition - I Kadek Warjaya; Margiasih Putri Liana; Muhammad Jauharul Wafi Taqiyyudin; Achmad Bahrul Ulum (Politeknik Negeri Malang, 2026)
In-wheel motor (IWM) systems in electric cars increase unsprung mass, which can have a detrimental effect on ride comfort and vehicle stability even though they enhance powertrain efficiency. The effectiveness of a Regenerative Tuned Mass Damper (RTMD) incorporated into an electric car suspension system under various road conditions is examined in this study through a numerical simulation approach. In order to assess vibration attenuation and energy regeneration performance under urban and rural road profiles, a quarter-car model with an electromagnetic energy harvesting circuit was created in MATLAB/Simulink. The Root Mean Square (RMS) acceleration of the sprung mass, along with the generated voltage, current, and electrical power output, were used to evaluate the RTMD performance. The findings demonstrate that under both road conditions, the suggested RTMD efficiently enhances vibration attenuation while concurrently harvesting electrical energy. With maximum vibration attenuations of 8.20% and 19.62%, respectively, the ideal RTMD mass for vibration reduction was 9 kg for the urban road profile and 13 kg for the rural road profile. Road roughness has a bigger impact on energy harvesting capabilities than vibration attenuation performance, as seen by the maximum collected power of 9.35 W under urban road circumstances and 126.72 W under rural road conditions. The absorber mass that maximised vibration attenuation was different from the absorber mass that produced the highest power output, indicating a trade-off between vibration suppression and electrical power generation. All things considered, the suggested RTMD shows great promise as a passive suspension augmentation technique that can both increase ride comfort and collect electrical energy from suspension vibrations in electric cars.